Analysis of INLISLite Management based on the COBIT 2019 DSS01 Domain at the Salatiga City Library and Archives Office - Capella Auriga Chrisanty; Suharyadi Suharyadi (SISTEMASI, 2026)
The utilization of information technology in library services plays a crucial role in improving operational efficiency and the quality of public services. The Salatiga City Library and Archives Office has implemented INLISLite as its integrated library automation system to support the management of library collections, membership, and circulation services. However, the effectiveness of the system largely depends on the quality of its operational management. This study aims to analyze the operational management of the INLISLite system based on the COBIT 2019 framework, specifically the DSS01 (Managed Operations) management objective. A qualitative descriptive research approach was employed, with data collected through interviews, observations, and document analysis. The evaluation focused on the five DSS01 management practices: Perform Operational Procedures, Manage Outsourced IT Services, Monitor IT Infrastructure and Operations, Manage Environmental Conditions, and Manage Facilities. The findings indicate that the operational management capability of INLISLite is predominantly at Capability Level 1 (Performed Process) for DSS01.01, DSS01.02, and DSS01.04, while DSS01.03 and DSS01.05 have achieved Capability Level 2 (Managed Process). These results suggest that although most operational processes have been implemented, they have not yet been fully standardized or systematically documented. Therefore, improvements are required through the development of dedicated Standard Operating Procedures (SOPs), enhanced IT infrastructure monitoring, strengthened management of outsourced IT services, improved supporting facilities, and more robust backup and risk mitigation procedures to achieve the target Capability Level 3 (Defined Process) in accordance with the IT governance principles of COBIT 2019.